Improving Student’s Speaking Ability by Using Speech Recognition Application at The Eighth Grade Students Of Madrasah Tsanawiyah - Bahtiarga, Defrin; Basya, Dihliza; Ghozali, Imam (Linguapedia, 2022)
Based on informal interview with the English teacher and preliminary study test of SMP Madrasah Tsanawiyah Miftahul Ulum Suco Lor had problem in speaking and it was shown by the average score of the preliminary test is 37% student get score more than 65. This study aimed to determine the learning process and the learning outcome of student’s speaking ability during the English conversation. The type of research is classroom action research (CAR). The Procedure used is the model cycle. Based on the results of the study, the percentage of students in the first cycle of activity individually obtained 58,5% and in the second cycle students’ activity individually obtained 95%. While the daily test results of students in the first cycle obtained average value 78,26% and 95,65% in the second cycle. It is proved that the learning process is a fan of student learning outcomes can be improved with the use of speech recognition application.